The Climate Security-Mobility Nexus: Impact Pathways and Research Priorities - Savelli, Adam; Schapendonk, Frans; Sarzana, Carolina; Dutta Gupta, Tanaya; Caroli, Giulia; Duffy, Mairead; de Brauw, Alan; Thornton, Philip K.; Pacillo, Grazia; Läderach, Peter R.D. (2022)
What are the interlinkages between climate change and variability, human mobility, and security? Where are the entry points for policies and programs that prevent climate-related mobility from causing conflict? What data gaps exist, and how can future research methodologies be designed to address them? Through a literature review of quantitative and qualitative literature on the climate-mobility-security nexus as well as an inward-facing portfolio review of CGIAR publications concerning the topic, this paper seeks to answer those questions and make recommendations to guide future research, policy priorities, and programming.